The National Truth Commission and the network of regional, local and sectorial commissions: the brazilian path - Seixas, Ivan Akselrud de (2016)
These are preliminary surveys of the network of state, municipal and sectorial truth commissions, a peculiarity established in Brazil as a result of the creation of the National Truth Commission in late 2012, of which they are branches. The text tries to show that this network has contributed significantly to the achievement of the goals of the National Commission. Indeed, it has given the Commission the means of having a capillary action in a country of continental dimensions, uniting and organizing efforts in the search for documents and in the organization of hearings, political acts and technical visits to sites related to human rights violations in Brazil during the period the law that created it has established – particularly the military dictatorship, from 1964 to 1985.